ANALISIS GARIS SEMPADAN BANGUNAN (STUDI KASUS JALAN SINDANGLAYA KOTA BANDUNG) - Mulyani, Hilmi - (Program Studi Arsitektur, Fakultas Teknik dan Informatika, Universitas PGRI Semarang, 2024)
The development of economic growth in the city of Bandung which is always increasing has an impact on the fulfillment of land and buildings to support commercial activities in the city of Bandung, especially on Jalan Sindanglaya, the city of Bandung which has an impact on the mismatch of building equivalent lines, especially on the front view of buildings, this is influenced by activities commercial businesses that are competing to reach the forefront of the road for the benefit of the commercial interests of the surrounding community, as well as the efficiency of commercial buildings that require a large enough area while land is limited. Where in fact the location of buildings that are not in accordance with the spatial plan is the reality of the current conditions. This research was conducted to analyze the incompatibility of the existing Building Border Lines with the currently applicable Regional Regulations. Data processing is carried out using the help of google maps and google earth to make it easier to pay for the building boundaries of each building and the outer boundaries of the road which will then be used to calculate the length of the building boundary lines in each existing building and are analyzed with the applicable regional regulations. The final result was that all the buildings in the case study were not in accordance with the existing Regional Regulations, where the average building violated was 14% or Â± 16 meters from the axle of the road. Judging from the many discrepancies, the authors provide recommendations, namely to amend the existing Regional Regulations in accordance with the conditions and policies that apply where the site is included in the main commercial area of the sub-district.